Exploring Environmental Inequalities among Marginalized Communities across the World - Carmichael, Ruthie (International Journal of Humanity and Social Sciences, 2023)
Purpose: The main objective of this study was to explore the pervasive issue of environmental inequalities that disproportionately impact marginalized communities. Methodology: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings revealed that there exists a contextual and methodological gap relating to issues of environmental inequalities that impact marginalized communities. The empirical review revealed the stark reality that marginalized communities, often characterized by low socioeconomic status and limited access to resources, bear the brunt of environmental hazards and injustices. These disparities are not only detrimental to the health and well-being of these communities but also perpetuate cycles of poverty and hinder their ability to thrive. The findings of this study emphasize the significance of formulating targeted policies and interventions to rectify the environmental injustices faced by marginalized communities. Addressing these disparities requires a multifaceted approach that takes into account the complex intersections of race, class, and environmental well-being. Unique Contribution to Theory, Practice and Policy: The Critical theory, Environmental Racism theory and the Intersectionality theory may be used to anchor future studies on environmental justice and marginalized communities. The study recommends that there is need for inclusive decision making that involves community members, there is need for investing in sustainable infrastructure and promoting environmental awareness among others.